ETHICAL ISSUES IN THE EVALUATION OF CLINICAL TRIALS DURING A PANDEMIC - COUDERC, Bettina (MEDECINE LEGALE DROIT MEDICAL, 2025)
In France, any application to conduct research involving humans (RIPH 1, 2 or 3) is evaluated by a committee for the protection of individuals (CPP). For specific cases of type 1 research (medicine, medical devices, etc.), an additional evaluation is carried out in parallel by the ANSM (French National Agency for the Safety of Medicines and Health Products). These two authorities are decision-making bodies since both must issue a positive opinion before clinical research can be initiated. PPCs are commonly referred to as ethics committees because they review research based on medical ethics. Their analyses require longer discussions than a simple scientific opinion since ethics is not fixed, and we generally leave the Manichean vision (yes/no). They evaluate, among other things, the following criteria: the honesty of the previous work that led to the proposal of the clinical trial (scientific integrity, beneficence); the methodology (adequacy between the objectives and the evaluation criteria: scientific honesty, non-maleficence), the beneficence and the foreseeable non-maleficence towards the included patient (absence of unjustified analyses); the adequacy of the human and material resources, the non-discrimination of certain patients and, above all, the fairness towards the patients (clarity of the information) and their protection (patient autonomy). During the pandemic (February 2020-June 2020) more than 500 test requests were filed with PPCs regarding COVID19 in addition to the usual requests. The French CPPs had to work in a hurry in order to allow, among other things, the rapid initiation of research involving humans concerning i) treatment, ii) means of mitigating the deleterious effects of infection, iii) means of preventing viral infection, iv) means of post-infection recovery, v) means of effective detection of the virus etc. Urgency did not affect the rigor of the evaluation. On the other hand, it has highlighted breaches of ethics by certain promoters and investigators which illustrate the problems encountered recurrently in the evaluations of clinical trials.